Exploring sequences and algebraic symbolism through an educational vídeo (Revista BOEM, 2024)
This experience report aims to present the construction and experience of an educational video about sequences and algebraic symbolism. This material was produced during the Professional Practice course of a mathematics degree program and experienced with a 7th-grade class of Elementary School. The development of the video followed the following steps: content selection, script creation, audio production, and scene development. Using the Canva platform, the video was developed to include illustrations, animations, and voice narration that explain the concepts visually and audibly. During the video experience, pauses were made for questions about numerical sequences, where students had moments to reflect and respond, with responses being collected, then the video presentation continued to present the answers. This interaction promoted student engagement, who showed interest and active participation. The assessment by the mathematics teacher of the Basic Education student group pointed out that the video has technical quality and pedagogical potential, suggesting that the use of this technological material can significantly enrich the teaching and learning of mathematical concepts.
Keywords: álgebra; mathematics; digital technologies; multimodality